Impact of Traffic Growth on Remaining Life of Rigid Pavement in Horizontal Curves - Oloan Sitohang; Teresia Lesiana Sianturi; Andar Sitohang; Piter L. Hutagalung (Advance Sustainable Science Engineering and Technology, 2026)
This study investigates the impact of traffic growth on the remaining design life of rigid pavement on horizontal curve. Increasing traffic volumes and frequent congestion on curved segments may accelerate pavement deterioration; however, limited studies that quantified traffic growth influences the remaining service life of rigid pavements. This research analyzes traffic survey data, subgrade CBR values, and axle load distribution collected from three horizontal curves along STA 34+000–35+625. Traffic enumeration using CCTV for seven days and analyzed using MDP 2024 method to estimate the reduction in pavement design life and potential structural damage. The results indicate a traffic growth rate of 6.53%, which reduced the remaining design life by 2.86 years (2023) and 6.22 years (2024). Fatigue cracking reached 2.22% while erosion damage reached 47.80%. These findings highlight the importance of integrating traffic growth considerations into rigid pavement design and maintenance planning to improve long-term pavement performance.